DFT study of CO adsorption on Pd-SnO2(110) surfaces - Bechthold, Pablo Ignacio (2015)
We studied the effect of Pd on the adsorption of CO on the tin oxide surface SnO2(110) by Density Functional Theory calculations. Molecular CO adsorbs more strongly in the presence of Pd pre-deposited on the surface. The most stable adsorption sites are those bonded to the Pd atom near a Pd top position on a tilted configuration. In this case the C-O distance increases, producing a bond weakening, and the calculated stretching frequency decreases. Analysis of the atomic orbital interactions reveals that Pd-CO bonding involves C s - O p and p orbitals from CO, with Pd d orbitals. For CO sites bonded to Pd, CO bonds to the surface producing a weakening on the surface Pd-O bond. The electronic configuration analysis shows that in all cases the CO molecule withdraws charge from the surface.